Hip-hop – what's in it for the academy? Self-understanding, pedagogy and aesthetical learning processes in everyday cultural Praxis. (2nd April 2016) - Söderman, Johan; Sernhede, Ove
Abstract : Since hip-hop first appeared in New York over 35 years ago, it has been associated with social activism and education. Accordingly, it is not surprising that academic institutions in universities and K-12 schools are interested in hip-hop. In this article, we will highlight the 'hip-hop academisation' and map out a new direction in a dialog between hip-hop and the academic world. By investigating the relation between hip-hop and pedagogy through interviews with prominent members of the hip-hop community in New York City as well as an analysis of 'universal', collective, and aesthetic learning processes in a local, Swedish youth-based hip-hop collective, we intend to open up a theoretical discourse on hip-hop and emancipatory pedagogy. Our empirical data are collected through ethnographical methods.